Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1007/s004180050378
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of nitrergic neurons in the myenteric plexus of rat stomach

Abstract: The effect of age on the proportion of nicotinamide adenine dinucleotide phosphate diaphorase (NADPHd)-positive neurons was investigated in the myenteric plexus of five different gastric areas of 1-day-, 1-week-, 2-week-, 1-month- and 2-month-old rats. Protein gene product 9.5 immunocytochemistry was used as a marker for the total enteric neuron population in order to establish the percentage of gastric nitrergic neurons in relation to age. The percentage of NADPHd-positive neurons in the proximal parts of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
1
11
0
1
Order By: Relevance
“…The onset and pace of development of nitrergic innervation are similar to adrenergic and cholinergic innervation and occur before peptidergic innervation. In the rat stomach, the percentage of NADPH diaphorase-positive neurons in the proximal part was higher than in the antral part (Timmermans et al, 1999). This difference persisted in groups of 1 day, 1 week, 2 weeks, 1 month, and 2 months of age.…”
Section: Development and Agingmentioning
confidence: 85%
“…The onset and pace of development of nitrergic innervation are similar to adrenergic and cholinergic innervation and occur before peptidergic innervation. In the rat stomach, the percentage of NADPH diaphorase-positive neurons in the proximal part was higher than in the antral part (Timmermans et al, 1999). This difference persisted in groups of 1 day, 1 week, 2 weeks, 1 month, and 2 months of age.…”
Section: Development and Agingmentioning
confidence: 85%
“…Although we have not quantitatively assessed the proportion, a good number of the approximately 35% NADPH diaphorase-positive and thus nitrergic neurons (Berthoud, 1995;Timmermans et al, 1999) receive functional vagal input. It has been convincingly shown that nitrergic neurons are responsible for the vagally mediated fundic relaxation response to accommodate ingested food (Desai et al, 1991).…”
Section: Organization Of Vagal Input To the Upper Gi-tractmentioning
confidence: 99%
“…NADH-diaphorase histochemical staining was earlier believed to stain all neurons in the ENS (Gabella 1987), but it was recently demonstrated that the techniques applied are not sufficiently accurate, and 20% of enteric neurons lack NADH-diaphorase (Young et al 1993). PGP 9.5, a neuronal form of ubiquitin, has been utilised as a general neuronal marker (Timmermans et al 1999), although PGP 9.5 immunoreactivity is present in only about 80% of all the myenteric neurons in the rat ENS (Eaker and Sallustio 1994). Neurofilament (NF) immunocytochemistry has been used to evaluate the entire enteric neuron population (Björklund et al 1984) and NF proteins such as NF 200 kDa or NF triplet protein were recently applied as general neuronal markers (Brehmer et al 1999a).…”
Section: Introductionmentioning
confidence: 98%